Difficulties experienced by women when collecting cytopathological exams (Research, Society and Development, 2020)
Objective: to analyze the factors associated with non-adherence to cytopathological examination by women. Method: This is an integrative review, whose research method is an essential tool, as it allows analysis through a literature review in a broad and systematic way, in addition to disseminating scientific data produced by other authors. Results: shame is an unfavorable factor for the exam and can cause interruption of care. Taking into account that the human body is exposed to the Pap smear process, the sensation of being easily hurt when touched and the judgment of others about its body is the instructive sensation of embarrassing intrusion, while strangers look at their body image. Conclusion: it is essential that women understand the importance of Pap smears to be performed regularly and understand the need for the test as a preventive method, not only when there are gynecological symptoms. Therefore, it is necessary for these women to start using preventive services to prevent the infection process from evolving to a more serious condition, which can lead to cervical cancer.